Labial Fusion in Childhood: Management and Treatment Strategies - Ayşe Filiz GÖKMEN KARASU; Çağlar ÇETİN (Bezmiâlem Science)
Labial fusion (LF) is frequently an asymptomatic condition and hypoestrogenism plays an important role in the pathopysiology. In the presence of a hypoestrogenic environment friction i.e. in the form of vigorous perineal cleaning leads to inflamation and desquamation of the epithelium which results in LF. Expectant management and reassurance of the family is key in asymptomatic patient. However if the condition results in complications such as urinary retention, recurrent urinary tract infection or vaginitis topical therapy with estrogen or bethametazone is the first treatment option. For patients who do not respond to a course of medical treatment or for cases in which recurrence occurs manuel or surgical seperation may be offered. Regardless of the choice of treatment the family should be counselled of the possibility of recurrence. Recurrence rates decrease with increasing age and the commence of endogenous estrogen production. Factors that contribute to recurrence are poor genital hygiene, recurrent vulvovaginitis and vulvar dermatoses.